Synthesis and spectroscopic characterization of functionalized indolenine derivatives / Abdul Qaiyum Ramle - Abdul Qaiyum , Ramle (2022)
This thesis focuses on the functionalization of substituted diformyl indolenines and their spectroscopic properties. The experimental works for the synthesis of four new series of indolenine derivatives are presented. The first series describes the reaction of diformyl indolenines with phenyl hydrazines to produce pyrazoles as the sole product. Treatment of pyrazole containing carboxylic acid with various substituted amino groups resulted in the formation of amide pyrazoles. The supramolecular packing of these pyrazoles was established by single X-ray crystallographic analysis. The second series reports the preparation of indoleninyl-barbiturate zwitterions. The unusual separation of charge between the iminium and enolate centers was elucidated by single X-ray crystallographic analysis. The presence of amino and carbonyl groups allows the zwitterions to be consolidated into a one-dimensional supramolecular layer via intermolecular hydrogen-bonding interactions. Notably, the absorption spectra showed a blue-shift with increasing solvent polarity. The presence of a small amount of TFA resulted in the protonation of the enolate center. The third series outlines the synthesis of indoleninyl-pyrimido[1,2-b]indazoles. The reaction was well-tolerated with a wide range of substituents on the indazole and indolenine rings. The optical properties of indoleninylpyrimido[ 1,2-b]indazoles were investigated. The final series of indolenines was formed by reacting diformyl indolenines with 4,5-bis(octyloxy)-1,2-diaminobenzene to generate dibenzotetraaza[14]annulenes (DBTAAs). The spectroscopic and computational analyses of these macrocycles were discussed in detail.